Case report: Heart transplant for persistent right heart failure after complete surgical repair and percutaneous closure of post-myocardial infarction ventricular septal rupture - Garg, Pankaj; Lykins, Amy; Alomari, Mohammad; Pollak, Peter; Patel, Parag; Sareyyupoglu, Basar (Frontiers in Cardiovascular Medicine, 2023)
The incidence of post-acute myocardial infarction ventricular septal rupture (post-AMI VSR) has decreased; however, mortality after surgical repair of post-AMI VSR remains high. Patients who are not surgical candidates can be managed by heart transplant with a good outcome. A heart transplant in a patient after successful repair of VSR has never been reported. We report a patient who had persistent right heart failure after the successful repair of VSR and underwent a heart transplant with a good outcome.